Respons Pertumbuhan dan Produktivitas Jagung BISI 18 terhadap Aplikasi Paclobutrazol dan Pupuk Nitrogen - Umi Alfia; Djarwatiningsih Pongki Soedjarwo; Agus Sulistyono (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2026)
[GROWTH AND YIELD OF BISI 18 MAIZE AS AFFECTED BY PACLOBUTRAZOL APPLICATION AND NITROGEN FERTILIZATION]. Maize (Zea mays L.) is a vital commodity in Indonesia that requires higher productivity. Tall-growing hybrid maize is prone to lodging; therefore, paclobutrazol can be used to suppress vegetative growth, while nitrogen supports plant growth and yield. This study aimed to determine the optimal paclobutrazol concentration and nitrogen fertilizer rate for the growth and yield of BISI 18 maize. The experiment was arranged in a split-plot design with two factors: paclobutrazol concentrations (0, 1250, 1500, and 1750 ppm) and nitrogen fertilizer rates (350, 400, 450, and 500 kg/ha). Paclobutrazol was applied as a foliar spray at 18 and 37 days after planting (DAP), while nitrogen fertilizer was applied by dibbling at 14, 35, and 49 DAP. Data were analyzed using analysis of variance (ANOVA) followed by the Honestly Significant Difference (HSD) test at the 5% level. The results showed a significant interaction between paclobutrazol concentration and nitrogen rate, with different optimal combinations for each parameter. The combination of 1750 ppm paclobutrazol and 350 kg/ha nitrogen produced the shortest plants, while 1750 ppm paclobutrazol with 450 kg/ha nitrogen resulted in the highest number of leaves. The earliest tasseling occurred with 1250 ppm paclobutrazol and 500 kg/ha nitrogen. A nitrogen rate of 450 kg/ha produced the highest grain weight per plant and per plot, increasing dry grain yield to 10.69 t/ha. Increasing paclobutrazol concentration suppressed plant height; however, excessive concentrations and nitrogen rates may inhibit growth. Paclobutrazol concentrations of 1250–1500 ppm combined with 450 kg/ha nitrogen were sufficient to achieve optimal growth and yield.